Does Criminal Thinking Predict Prison Misconduct? An Evaluation of TCU’s Criminal Thinking Scales - Duwe, Grant (Criminal justice and behavior, 2023)
To date, only one published study has tested the predictive validity of the Texas Christian University–Criminal Thinking Scales (TCU-CTS), and no studies have tested whether these scales are predictive of prison misconduct. Using a sample of more than 2,000 people incarcerated in Minnesota’s prison system, this study examined the predictive validity of the TCU-CTS with multiple measures of prison misconduct. The results showed the overall TCU-CTS score significantly predicted misconduct, although the strength of this association was relatively modest (AUC = 0.62). Among the six scales on the TCU-CTS, Cold-Heartedness significantly predicted both measures of misconduct, whereas Power Orientation and Criminal Rationalization were each significantly associated with one misconduct measure.